Genetic Engineering in the Light of Dialectics of Enlightenment - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2015)
This article presents the ambivalent character of the Enlightenment’s legacy, which aside from promised progress brought also new dangers. The essay also presents historical examples of creating “new world” and “new human” and dangers connecting with these attempts. The biggest contemporary challenge concerning this issue is using genetic engineering. The most dangerous contemporary threat for homo oecologicus and “ecozoic era” is applying of violence and creating “ecological totalitarianism.” The hope for the restoration of a ravaged world gives philosophical reflection and biological potential of man for recognizing values and sense of the world. One interesting solution is K.M. Meyer-Abich’s concept of “ecological revolution.”